Metamorphic Fasies of Metamorphic Rocks in the Mekongga Complex, Loea Region, East Kolaka Regency, Southeast Sulawesi Province - Sugiono; Hasria; S. Asfar; L. O. Ngkoimani; Muliddin (International Journal of Acta Material, 2026)
Metamorphic rocks in the study area are part of the Mekongga Metamorphic Complex which is Carbon age. It was interpreted as part of the Malihan complex in southeast sulawesi arm. Administratively located in the area of Loea, Kolaka Timur district, Southeast Sulawesi. Geographically located in coordinates 121°53'0"-121°54'30"(BT) and 04°04'0"- 04°05'30" (LS). The purpose of this research is to identify the types of rock and metamorphic facies present in the Loea area. The research sample is used for petrographic analysis to determine rock types and their mineral composition. The result of petrography analysis shows that the study consisted of metamorphic rocks, namely muscovite schist, muscovite-quartz schist, and graphite-quartz schist, has texture in schistose texture, a lepidoblastic mineral form, and mineral composition that consists of quartz, muscovite, biotite, chlorite, graphite, and opaque minerals. Mineralogical data of metamorphic rock indicate that the metamorphic facies in the research area is greenschist, with muscovite, chlorite, and quartz as its constituent minerals, formed at 300˚C-400˚C.